Studying the Medication Prescribing Errors in the Egyptian Community Pharmacies - Abuelsoud, Nermeen (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: Prescribing medication errors rates and consequences are not well studied in the Egyptian community pharmacies. These errors may have clinically significant consequences and associated with serious adverse events. Errors determination is difficult because prescriptions may not be available for review and patients often refill the medications from different pharmacies. The Primary Objectives: (i) To assess and identify the rates and categories of drug prescribing errors in the Egyptian community pharmacies and (ii) to detect the specialties associated with high incidences of prescribing errors in the Egyptian community. By the end of this study, a secondary objective was achieved as the students became able to implement the clinical pharmacy concepts in the Egyptian community pharmacies. Materials and Methods: This was a retrospective study conducted on different Egyptian community pharmacies over a period of 3 months. The prescriptions from different pharmacies were collected and analyzed to detect the presence of any medication prescribing error. Results: This study was conducted on a total of 810 prescriptions with a total number of 3262 medications. The total detected medication prescribing errors were 19,405. Inappropriate medication use errors accounted for 9% of these errors. Drug interactions (39%) were the most frequently identified error type in these errors followed by errors in dosing frequency of administration (29%). Conclusion: Strategies should be developed to detect and limit these errors in the Egyptian community. Training courses should be conducted to improve the prescribing skills of the physicians and the pharmacists’ skills in medication prescribing errors detection.